SNP markers revealed the genetic diversity and population structure of Mesosphaerum suaveolens (L.) Kuntze Syn. Hyptis suaveolens (L.) Poit accessions collected in Benin - Armel Frida Dossa; Dèdéou A. Tchokponhoué; Aristide Carlos Houdegbe; Enoch G. Achigan-Dako (PLoS ONE, 2025)
Mesosphaerum suaveolens (L.) Kuntze is a wild species with many biological activities in medicine. The species can potentially serve as a pesticide in agriculture thanks to its high content of volatile compounds. However, knowledge of the species’ genetic diversity and population structure is currently scarce, thus hindering improvement and conservation initiatives. This research used single nucleotide polymorphism (SNP) genotyping to study the diversity and population structure of 175 Mesosphaerum suaveolens collected from the three phytogeographical zones of Benin. Our study reports 3,613 high-quality SNP markers for M. suaveolens. Based on the markers, a mean polymorphism information content of 0.28, a low expected heterozygosity (He = 0.287) coupled with low genetic differentiation (Fst = 0.007) were observed in the species. The overall average value of observed heterozygosity (Ho) was 0.11. The Neighbor-joining analysis identified three subpopulations, whereas two mixed subpopulations were detected via population structure analysis. The results of the molecular variance analysis revealed that differences among samples within populations accounted for the majority of genetic variation (59.3%). The population from the Sudanian region presented the highest genetic diversity (He = 0.293), whereas the Guineo-congolian population presented the lowest genetic diversity (Ho = 0.278). These results pave the way for informed conservation in M. suaveolens and highlight the need to expand the genetic base of this species for upcoming improvement initiatives. However, reference genome and genome-wide association studies (GWAS) to associate genomic and morphological or chemical constituents are needed.